2017
DOI: 10.1002/jmv.24832
|View full text |Cite
|
Sign up to set email alerts
|

Marburg virus‐like particles produced in insect cells induce neutralizing antibodies in rhesus macaques

Abstract: Marburg virus (MARV), which is one of the most virulent agents in the world, causes lethal haemorrhagic fever in humans and nonhuman primates (NHPs) with a mortality rate of up to 90%. Currently, there is no effective treatment or approved vaccine for MARV for human use to control disease outbreak and spread. Virus-like particles (VLPs), which are morphologically identical to the native infectious virus particle, are efficacious as vaccines against many viruses, including human papilloma virus (HPV), porcine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These structural differences may explain why none of the current MARV vaccines can induce effective neutralizing antibodies. Gai et al prepared virus-like particles assembled from GP and VP40 using the insect cell expression system [ 57 ]. VLP and Poria cocos polysaccharide (PCP-II) adjuvant was able to induce antibodies with pseudovirus neutralizing activity in rhesus monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…These structural differences may explain why none of the current MARV vaccines can induce effective neutralizing antibodies. Gai et al prepared virus-like particles assembled from GP and VP40 using the insect cell expression system [ 57 ]. VLP and Poria cocos polysaccharide (PCP-II) adjuvant was able to induce antibodies with pseudovirus neutralizing activity in rhesus monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of PCP-II combined with MARV VLP was further evaluated in primate rhesus monkeys. The results showed that MARV VLPs mixed with PCP-II had excellent immunogenicity in rhesus monkeys [ 83 ].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Vaccine adjuvant [82,83] Table 2. Antiviral activities of medicinal fungi and their mechanism of action in plant and animal viruses.…”
Section: Poria Cocosmentioning
confidence: 99%
“…VLP-based vaccines have demonstrated significant success against MARV in NHPs. These studies indicate that mVLP vaccines can effectively induce binding antibodies, neutralizing antibody effects, and T-cell responses, all crucial components of adaptive immunity [22][23][24]. DNA-GP vaccines have been explored with positive results.…”
Section: Rvsv-marv-gpmentioning
confidence: 98%